Mediating effect of customer perceive value on experience quality and loyalty relationship - SUBALI PATMA, TUNDUNG; KUSUMAWATI, ANDRIANI; MAULUDIN, HANIF; ZAINI, ACHMAD (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This research is a quantitative approach to explanatory research. The survey was conducted using a questionnaire and analyzed using the equations of structural equation modeling (SEM)-based partial least square (PLS). The sample of this research totaled 168 respondents based on predetermined criteria. This research study is based on the theory of contribution understanding and management of outdoor coffee shops. The results of this research indicate directly experience the quality effect on customer perceived value and customer loyalty. The research indicates that the customer perceived value does not provide mediation between the effects of variable quality experience with customer loyalty. RESUMEN Esta investigación es un enfoque cuantitativo para la investigación explicativa. La encuesta se realizó mediante un cuestionario y se analizó utilizando las ecuaciones del mínimo cuadrado parcial (PLS) basado en el modelado de ecuaciones estructurales (SEM). La muestra de esta investigación totalizó 168 encuestados con base en criterios predeterminados. Este estudio de investigación es sobre la teoría de la comprensión de la contribución y la gestión de la cafetería. Los resultados de esta investigación indican la experiencia directa del efecto de calidad en el valor percibido y la lealtad del cliente. La investigación indica que el valor percibido por el cliente no proporciona mediación entre los efectos de la experiencia de calidad variable con la lealtad del cliente.